A Series of Unfortunate Events: The Carnivorous Carnival - Book 9 - Snicket, Lemony (New York : HarperCollins, 2002)
On the run as suspected murderers, the unlucky Baudelaire orphans find themselves trapped in the Caligari Carnival, where they must masquerade as freaks in order to hide from the evil Count Olaf.
Keywords: Orphans -- Fiction; Brothers and sisters -- Fiction; Carnivals -- Fiction; Humorous Stories